REACH THE STARS: HOW TO MANAGE HUMAN RESOURCES SUCCESSFULLY IN EARLY CHILDHOOD EDUCATION CENTER? - Ajeng Regita Maudy; Misno A. Lathif; Senny Weyara Dienda Saputri (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2020)
This research is motivated by the success of the PAUD Terpadu Al Furqan Jember in developing students' potential, academic, and non-academic achievements. This success cannot be separated from human resource management, especially teachers as educators. This study aimed to determine the process of human resource management for teaching staff at PAUD Terpadu Al Furqan Jember. This type of research is descriptive qualitative with observation, interviews, and documentation as data collection methods. The results showed that the human resource management process in PAUD Terpadu Al Furqan Jember was carried out in planning, organizing, developing, and evaluating. The planning stage began with a needs analysis by the principal, followed by recruitment by the foundation. The principal's organizing stage is carried out by coordinating human resources' placement according to expertise and the appointment of a companion teacher to assist the apprenticeship program for new teachers. Schools and foundations carry out the development stage in competency improvement and quality control activities, routinely held every Saturday. The evaluation phase is carried out once a week after development activities and at the end of each semester carried out by the principal, peers, and parents. The evaluation results' follow-up is the existence of coaching carried out by the foundation and the school in constructive personal criticism, followed by training attended by all human resources.